2020
DOI: 10.1016/j.cell.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA Promotes Efficient Extracellular Electron Transfer by Pyocyanin in Pseudomonas aeruginosa Biofilms

Abstract: Highlights d PYO and PCN bind extracellular DNA, which facilitates their retention in biofilms d Electrode biofilms support fast PYO electron transfer and slow PYO loss d Phenazines rapidly exchange electrons and are capable of DNA charge transfer in vitro

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 81 publications
0
97
0
Order By: Relevance
“…Alternatively, the observed increased tolerance to tobramycin in that study might not be related to molecular defenses induced by phenazines, but rather phenazine-mediated physiological differences under the studied conditions [ 17 ]. Phenazines are redox-active molecules that can promote metabolic activity under oxygen limitation, which occurs within biofilms [ 12 , 17 , 69 ]; the specific details of how such metabolic activity might affect antibiotic tolerance merit further attention. The other previous study found that PYO increased planktonic culture cell densities in the presence of various antibiotics [ 18 ], but these experiments did not directly demonstrate an effect on antibiotic tolerance (i.e., the ability to survive an otherwise lethal antibiotic treatment) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the observed increased tolerance to tobramycin in that study might not be related to molecular defenses induced by phenazines, but rather phenazine-mediated physiological differences under the studied conditions [ 17 ]. Phenazines are redox-active molecules that can promote metabolic activity under oxygen limitation, which occurs within biofilms [ 12 , 17 , 69 ]; the specific details of how such metabolic activity might affect antibiotic tolerance merit further attention. The other previous study found that PYO increased planktonic culture cell densities in the presence of various antibiotics [ 18 ], but these experiments did not directly demonstrate an effect on antibiotic tolerance (i.e., the ability to survive an otherwise lethal antibiotic treatment) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa produces several redox-active, heterocyclic compounds known as phenazines [10]. Phenazines have been shown to provide multiple benefits for their producers, including by (i) serving as an alternative electron acceptor in the absence of oxygen, thereby promoting redox homeostasis and anaerobic survival [11], which is particularly relevant for oxidant-limited biofilms [12]; (ii) acting as signaling molecules [13]; (iii) promoting iron acquisition [14]; and (iv) killing competitor species [15]. In addition, despite possessing broad-spectrum antimicrobial activity [10], including against P. aeruginosa itself [16], phenazines have recently been shown to promote tolerance to clinical antibiotics under some circumstances, via mechanisms that have yet to be characterized [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are usually embedded in a self-produced matrix to form biofilm, and the complex architecture of a biofilm is maintained by an extracellular matrix of EPSs, proteins, and eDNA ( Flemming and Wingender, 2010 ; Candela et al, 2019 ). The function of eDNA in biofilms has attracted much attention in recent years ( Okshevsky et al, 2015 ; Saunders et al, 2020 ). Bacillus cereus follows this rule, and its matrix contains all three components ( Majed et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Saunders et al suggest that pyocyanin plays an important role in the metabolism of P . aeruginosa biofilm due to its participation in charge transfer processes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that pyocyanin exerts minor toxic events in the range of 5-10 mg/L in lung epithelial cells (L-132) [13]. Additionally, Saunders et al suggest that pyocyanin plays an important role in the metabolism of P. aeruginosa biofilm due to its participation in charge transfer processes [14].…”
Section: Introductionmentioning
confidence: 99%